The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/2331216518807400
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Approach for Auditory Profiling and Characterization of Individual Hearing Loss

Abstract: Pure-tone audiometry still represents the main measure to characterize individual hearing loss and the basis for hearing-aid fitting. However, the perceptual consequences of hearing loss are typically associated not only with a loss of sensitivity but also with a loss of clarity that is not captured by the audiogram. A detailed characterization of a hearing loss may be complex and needs to be simplified to efficiently explore the specific compensation needs of the individual listener. Here, it is hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…Recently, Sanchez-Lopez et al (2018) proposed a data-driven method for auditory profiling that was tested and verified by analyzing two data sets from previous experimental studies (Johannesen et al, 2016;Thorup et al, 2016). Thorup et al (2016)'s data set was collected in a clinical setup using listeners with either near-normal audiometric thresholds (26 listeners), obscure dysfunction (4 listeners), or mild-to-moderate high-frequency hearing loss (29 listeners).…”
mentioning
confidence: 99%
“…Recently, Sanchez-Lopez et al (2018) proposed a data-driven method for auditory profiling that was tested and verified by analyzing two data sets from previous experimental studies (Johannesen et al, 2016;Thorup et al, 2016). Thorup et al (2016)'s data set was collected in a clinical setup using listeners with either near-normal audiometric thresholds (26 listeners), obscure dysfunction (4 listeners), or mild-to-moderate high-frequency hearing loss (29 listeners).…”
mentioning
confidence: 99%
“…While the diotic condition can be resolved monoaurally, the dichotic condition requires the binaural processing abilities to be sufficiently intact to detect the contour. Previous studies showed that some listeners were unable to detect binaural pitch, regardless of the audiometric configuration (Sanchez-Lopez et al, 2018;Santurette & Dau, 2012). Therefore, it was of interest to compare the results of these two binaural processing tests.…”
Section: Binaural Processing Abilitiesmentioning
confidence: 99%
“…Sanchez-Lopez et al 2020In Denmark, the Better hEAring Rehabilitation (BEAR) project was initiated with the aim of developing new diagnostic tests and hearing-aid compensation strategies for audiological practice. Although the assessment of individual hearing deficits can be complex, new evidence suggests that the perceptual consequences of a hearing loss can be characterized effectively by two types of hearing deficits, defined as "auditory distortions" (Sanchez-Lopez, Bianchi, Fereczkowski, Santurette, & Dau, 2018). By analysing the outcomes of two previous studies (Johannesen et al, 2016;Thorup et al, 2016) with a data-driven approach, Sanchez-Lopez et al (2018) identified highfrequency hearing loss as the main predictor of one of the distortions, whereas the definition of the second type of distortion was inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision tree model, as a basic machine learning form, is playing an increasingly important role in healthcare applications. Specifically in the hearing science field, this technique has been used to seek the optimal suprathreshold test battery to classify auditory profiles towards effective hearing loss compensations [31]. More frequent applications of a decision tree analysis were evaluating whether a medical and audiological practice is cost-effective, for example, implanting cochlear prosthesis [32], the pursuit of magnetic resonance imaging (MRI) with or without contrast in the workup of undifferentiated asymmetrical sensorineural hearing loss [33], and universal or selective hearing screening on newborns [34, 35].…”
Section: Introductionmentioning
confidence: 99%